Comparison of feeding calves vs. yearlings - Hickok, D.T.; Schalles, R.R.; Franke, D.E.; Dikeman, Michael E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Data from the 207 crossbred steers used in this study indicate that when calves are placed in the feedlot on a finishing ration at weaning, they will have better feed efficiencies, greater lifetime ADGs, lighter carcass weights, and equal carcass qualities compared to those placed as yearlings. In recent times, heavy carcass weights have been rather common in the industry. Every over-weight steer had a desirable weight at one time, and this study shows that they would have produced a desirable carcass if managed correctly.
Keywords: Beef; Cattle; Management; Performance; Carcass; Systems